2012
DOI: 10.1016/j.ydbio.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Akt is negatively regulated by Hippo signaling for growth inhibition in Drosophila

Abstract: Tissue growth is achieved through coordinated cellular growth, cell division and apoptosis. Hippo signaling is critical for monitoring tissue growth during animal development. Loss of Hippo signaling leads to tissue overgrowth due to continuous cell proliferation and block of apoptosis. As cells lacking Hippo signaling are similar in size compared to normal cells, cellular growth must be properly maintained in Hippo signaling-deficient cells. However, it is not clear how Hippo signaling might regulate cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…However, whether YAP acts as an upstream regulator of C-myc, CDKs and Caspase3 to regulate cell proliferation and apoptosis is essential and needs further exploring. Besides, Hippo signaling negatively regulates Akt expression through Yki inhibition in Drosophila [53]. Our results suggested that the function of CD44 in cell proliferation and apoptosis might be related to YAP regulation.…”
Section: Discussionmentioning
confidence: 65%
“…However, whether YAP acts as an upstream regulator of C-myc, CDKs and Caspase3 to regulate cell proliferation and apoptosis is essential and needs further exploring. Besides, Hippo signaling negatively regulates Akt expression through Yki inhibition in Drosophila [53]. Our results suggested that the function of CD44 in cell proliferation and apoptosis might be related to YAP regulation.…”
Section: Discussionmentioning
confidence: 65%
“…Consistently, knockout of MST1/2 or Sav in the liver or heart also induced organ size (Zhou et al 2009;Lee et al 2010;Lu et al 2010;Song et al 2010;Heallen et al 2011). Recently, a connection between the Hippo pathway and the PI3K-TOR pathway has been demonstrated (Strassburger et al 2012;Tumaneng et al 2012b;Ye et al 2012). This is significant because TOR signaling is important in cell growth; thus, the Hippo pathway may control organ size in part by modulating cell growth ( Fig.…”
Section: Regulation Of the Hippo Pathway: Implications In Physiologicmentioning
confidence: 60%
“…6K). This finding suggests a delicate balance between growth rates and signaling in generating a normal wing because gross up-regulation or down-regulation of the PI3K pathway simply increases/decreases the size of the wing (47). However, we cannot exclude the possibility that PI3K also affects Wg signaling via Akt repression.…”
Section: Wg Is Internalized Via a Garz-mediated Endocytic Pathway In mentioning
confidence: 93%